Produção e concentração de enzimas hidrolíticas a partir de Beauveria bassiana - Alves, Eliana Albornoz (2018)
The fungus Beauveria bassiana has been prominent in the production of infection structures and in the synthesis of a cocktail of proteins, enzymes, organic acids and secondary bioactive metabolites, responsible for the entomopathogenic activity and virulence. Thus, the aim of this work was to produce via solid-state and submerged fermentation, to concentrate and characterize hydrolytic enzymes (chitinase, β-1,3-glucanase, endocellulase and exocellulase) by Beauveria bassiana. Enzyme activity was superior in solid substrate when compared to submerged, being 52,5% higher for exocellulase, 22,0% for endocellulase and 18,1% for β-1,3-glucanase, but chitinase activity remained the same. The ultrafiltration was more efficient when used a 10 kDa membrane, a pressure of 4 bar and the ratio of permeate and retentate of 1:1. The possibility of membrane reuse using an oxidant cleaning solution was viable only for one reuse. Furthermore, the enzymes were highly stable at 40°C, being more thermostable at higher temperatures. In lower acid media, enzymes were more unstable, with pH 4 being more suitable to maintain their activity for longer periods of time. Finally, the application of the permeate fraction in Phereoeca uterella (household casebearer) larvae showed better results. The higher concentration of hydrolytic enzymes, mainly chitinase, present in this fraction facilitated the degradation of the insect cell wall. This study opens up space for more in-depth work on the optimization of process conditions, promising results for the possibility of scale-up.